Effects caused by antiferroelectric nanodomains in PZT-based coarse-grained ceramics with compositions from the morphotropic boundary region - V. M. Ishchuk; D. V. Kuzenko; V. L. Sobolev (Journal of Advanced Dielectrics, 2017)
Presented results demonstrate importance of taking into account such a phenomenon as the solid solution decomposition at the boundaries separating coexisting phases in lead zirconate-titanate-based solid solutions with compositions belonging to the morphotropic boundary region of the “temperature–composition” phase diagram. It is shown that in the local decomposition of solid solutions in the vicinity of the boundaries separating the tetragonal and rhombohedral phases in lead zirconate-titanate-based solid solutions lead to the changes of the solid solution’s chemical composition and to the formation of segregates. It is also shown that the proper thermoelectric treatment of samples containing these segregates can give substantially higher values of piezoelectric parameters in the lead zirconate-titanate-based compounds.